The impact of e-commerce platform usage on the economic benefits of SMEs in Indonesia during the pandemic - Lesmana, Muftia (Privietlab, 2025)
This study examines how the effectiveness of e-commerce platforms influenced the economic benefits of SMEs in Indonesia during the pandemic. This study investigates whether the pandemic, coupled with a higher intensity of e-commerce usage than usual, contributed to economic gains for SMEs. This study proposes a new model developed from Tran (2021) by incorporating additional variables such as perceived benefits, perceived supply chain, perceived organizational resources, e-service quality, and external pressure, while also examining the impact of PEEP on economic benefits and the digital transformation process, especially during the pandemic. The researchers conducted an online survey using Google Forms, targeting SME entrepreneurs who use e-commerce platforms to conduct business. A total of 270 responses were obtained. Hypothesis testing was performed using Partial Least Squares (PLS) analysis with Smart PLS 4.0. The results indicate that pandemic fear during online sales positively moderates the relationship between PEEP and economic benefits, and similarly moderates the relationships between perceived benefits, perceived supply chain, perceived organizational resources, e-service quality, and external pressure and economic benefits.